DEVELOPMENT AND VALIDATION OF AN HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE DETERMINATION OF 17-Β ESTRADIOL IN POLYMERIC NANOPARTICLES - KOGA, ADRIANA YURIKO; CARLETTO, BRUNA; LIPINSKI, LEANDRO CAVALCANTE; KLEIN, TRAUDI; FARAGO, PAULO VITOR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: A simple high-performace liquid chromatography method was developed and validated to determine 17-β estradiol in poly (ε-caprolactone) nanocapsules. Methods: The chromatographic conditions were as follows: C18 GL column with a mobile phase of acetonitrile:water (92:8 v/v) at flow rate of 1.5 mL/min with detection at 280 nm. The evaluated parameters were specificity, linearity, limits of detection and quantification, precision, accuracy, and robustness. Results: The method was specific and linear (r=0.9982). The limits of detection and quantification were 5.78 μg.mL-1 and 17.54 μg.mL-1, respectively. Suitable accurancy and robustness were obtained. The stability assay showed that pH variation occured after 120 days of storage, and no changes were observed regarding the size and polydispersion parameters. The applicability of the method was evaluated by determining the encapsulation efficiency of the E2 nanocapsules after 120 days of storage. The results showed values >99%. Conclusion: The results demonstrated the applicability of the developed and validated analytical method.